Forensic accounting and the current state of the infrastructure components of its implementation - Matar, Osama Issam (Journal of Economic, Administrative and Legal Sciences, 2023)
Forensic accounting is a specialized accounting field that deals with the detection and Prevention of financial fraud and employee crimes. It involves the use of accounting, auditing and investigative skills to analyze financial transactions and provide evidence in legal proceedings. The importance of criminal accounting has increased significantly in recent years due to the high number of cases of financial fraud around the world , and the application of Forensic accounting depends heavily on the state of the infrastructure components, we aim in this study to study the Forensic accounting infrastructure and find out the reasons that required criminal accounting and the infrastructure that should be available in the Forensic accountant and understanding the difference between the Forensic accountant and the independent auditor and the knowledge of the essence of the elements of Forensic accounting as an element of the registration system and cause of technology has facilitated the way to commit thıs kınd of crimes and that is why the number of financial crimes has increased, it is necessary to know the technology and techniques that Infrastructure for Forensic accounting.
Keywords: Forensic accounting; infrastructure components